Mechanism Design With Ambiguous Communication Devices - Bose, Subir; Renou, Ludovic (Econometrica, 2014)
This paper considers mechanism design problems in environments with ambiguity-sensitive individuals. The novel idea is to introduce ambiguity in mechanisms so as to exploit the ambiguity sensitivity of individuals. Deliberate engineering of ambiguity, through ambiguous mediated communication, can allow (partial) implementation of social choice functions that are not incentive compatible with respect to prior beliefs. We provide a complete characterization of social choice functions partially implementable by ambiguous mechanisms.